CONTRIBUTING FACTORS TO MEDICATION ERRORS AS PERCEIVED BY NURSING STUDENTS IN ILIGAN CITY, PHILIPPINES - Khandy Lorraine Guerrero Apsay; Gianille Geselle Alvarado; Marlon Charles Paguntalan; Sittie Hannah Tumog (Belitung Nursing Journal, 2018)
Background: Nursing students are allowed to give medication with clinical supervision to enhance skills in medication administration. However, studies suggest that some students commit medication errors due to knowledge, personal, administrative and environmental factors. Objective: This study will identify factors that cause student nurses to commit medication errors and correlate it to the number of perceived medication errors committed. Methods: A correlational design was used to correlate the factors contributing to medication administration and the number of medication errors committed by the students. 388 randomly selected nursing students were asked to answer Modified Medication Error Questionnaire which measures the knowledge, administrative, personal and environmental factors which may contribute to medication administration errors. Medication administration errors are measured according to the number of times a student commits as perceived by them. Results: Lack of knowledge of the drug and equipment to be used for administration, decrease in confidence, poor clinical assessment of patients’ conditions, and poor follow ups from clinical instructor are identified concerns under knowledge factor. Poor positive feedback, inadequate supervision and belittling ways of clinical instructors are identified under the administrative factor. Fear of administering an injection or giving medications is a common problem under personal factor. Inappropriate labelling of medications, unfavorable room temperature, lack of space, inadequate lighting, disorganized medication administration schedule and noise are problems found under environmental factor. A minority of 17.3% claimed that they have encountered a medication error in any of their clinical duties. Conclusion: Knowledge, administrative, personal and environmental factors have no effect towards medication errors. However, the relationship between age and the number of perceived medications errors is established. More in-depth investigation is recommended to determine the type of medication errors committed and its detrimental effects towards patient safety.